Knowledge of drugstore attendants of Ribeirão Preto about gonorrhoeae - Gir, Elucir; Duarte, Geraldo; Pinto, Valdir M.; Machado, Juliana P.; Reis, Renata K.; Carvalho, Milton J. (Brazilian Journal of Sexually Transmitted Diseases, 2003)
[...]